EFFECT OF JOB SATISFACTION, EMPLOYEE LOYALTY AND EMPLOYEE COMMITMENT ON LEADERSHIP STYLE (HUMAN RESOURCE LITERATURE STUDY) - Saputra, Farhan; M Rizky Mahaputra (Dinasti Publisher, 2022)
The Literature Review article on the Effect of Job Satisfaction, Employee Loyalty and Employee Commitment to Leadership Style is a scientific article that aims to build a research hypothesis on the influence between variables which will be used in further research, within the scope of Human Resource Management. The method of writing this Literature Review article is the library research method, which is sourced from the online media Google Scholar and uses Mendeley as a reference. The results of this Literature Review article are that: 1) Job Satisfaction has an effect on Leadership Style; 2) Employee Loyalty has an effect on Leadership Style; and 3) Employee Commitment has an effect on Leadership Style. Apart from these 3 independent variables that affect endogenous variables, there are other factors including salary, work environment and work culture variables.